Assessment of Gene Flow to Wild Relatives and Nutritional Composition of Sugarcane in Brazil - Bressan, Eduardo Andrade; Carvalho, Igor Araújo Santos de; Borges, Maria Teresa Mendes Ribeiro; Carneiro, Monalisa Sampaio; Silva, Edson Ferreira da; Gazaffi, Rodrigo; Shirasuna, Regina Tomoko; Abreu, Vinícius; Popin, Rafael V.; Figueira, Antonio; Oliveira, Giancarlo Conde Xavier (Frontiers in Bioengineering and Biotechnology, 2020)
The commercial release of genetically modified organisms requires the prior environmental and human/animal health risk assessment. In Brazil, the National Biosafety Authority (CTNBio) demands to survey the area of natural occurrence of wild relatives of the GMO in the Brazilian ecosystems to evaluate the possibility of introgressive hybridization between sexually compatible species. Modern sugarcane cultivars, the focus of this study, derive from a series of hybridization and backcrossing events among Saccharum species. The so-called “Saccharum broad sense” includes around 40 species from a few genera, including Erianthus, found in various tropical regions. In Brazil, three native species, originally considered as belonging to Erianthus, were reclassified as S. angustifolium (Nees) Trin., S. asperum (Nees) Steud., and S. villosum Steud., based on inflorescence morphology. Thus, we have investigated the potential occurrence of gene flow among the Brazilian Saccharum native species and commercial hybrids as a requisite for GMO commercial release. A comprehensive survey was carried out to map the three native Saccharum species in Brazil, concluding that they are sympatric with sugarcane cultivation only from around 14°S southwards, which excludes most Northeastern sugarcane-producing states from the possibility of introgression. Based on phenology, we concluded that the Brazilian Saccharum species are unable to outcross naturally with commercial sugarcane and that the overlap between the flowering periods of sugarcane and the native species is limited. A cpDNA-based phylogenomic reconstruction showed that the three native Saccharum species are the closest taxa to sugarcane in Brazil, being closer than introduced Erianthus or Miscanthus. A two-year study on the nutritional composition of the 20 main sugarcane cultivars planted in Brazil was carried out. The information generated will be included in a publicly available database (ILSI) to be used in future substantial equivalence studies for genetically modified cultivars. Besides a considerable amount of genetic variation and plastic responses, many instances of genotype-by-environment interaction were found. The combined results generated to date indicate that the release of transgenic sugarcane cultivars in the Brazilian territory can be considered biosafe.